Cxcl9-11 Chemokines and cxcr3 Receptor in Teleost Fish Species - Imarai-Bahamonde, C; Valdes-Parra, N; Reyes-Lopez, F; Barraza-Rojas, F (Elsevier Ltd, 2022)
The coordinated migration of immune cells from lymphoid organs to in or out of the bloodstream, and towards the site of infection or tissue damage is fundamental for an efficient innate and adaptive immune response. Interestingly, an essential part of this movement is mediated by chemoattractant cytokines called chemokines. Although the nature and function of chemokines and their receptors are well documented in mammals, much research is needed to accomplish a similar level of understanding of the role of chemokines in fish immunity. The first chemokine gene identified in teleosts (rainbow trout, Oncorhynchus mykiss) was CK1 in 1998. Since then, the identification of fish chemokine orthologue genes and characterization of their role has been more complex than expected, primarily because of the whole genome duplication processes occurring in fish, and because chemokines evolve faster than other immune genes. Some of the most studied chemokines are CXCL9, CXCL10, CXCL11, and the CXCR3 receptor, all involved in T cell migration and in the induction of the T helper 1 (Th1) immune response. Data from the zebrafish and rainbow trout CXCL9-11/CXCR3 axis suggest that these chemokines and the receptor arose early in evolution and must be present in most teleost fish. However, the pieces of knowledge also indicate that different numbers of gene copies can be present in different species, with distinct regulatory expression mechanisms and probably, also with different roles, as the differential expression in fish tissues suggest. Here, we revised the current knowledge of the CXCL9-11/CXCR3 axis in teleost fishes, identifying the gaps in knowledge, and raising some hypotheses for the role of CXCL9, CXCL10 CXCL11, and CXCR3 receptor axis in fish, which can encourage further studies in the field. © 2022 The Authors